Comparison between the use of open and walled platforms by juvenile blue foxes (Alopex lagopus) - Korhonen, Hannu T.; Niemelä, Paavo (Agricultural Research Centre of Finland, 1996)
Tutkimuksessa selvitettiin, missä määrin kettujen hyllynkäyttöön vaikuttaa se, onko näkyvyys ympäristöön estetty seinien avulla. Hyllynkäyttöä mitattiin videokameralaitteiston ja otoshavannoinnin avulla vieroituksesta nahkontaan. Kokeessa oli kaksi hyllytyyppiä: toinen seinällinen ja toinen seinätön (molemmissa 16 urosta ja 14 naarasta). Tulokset olivat samansuuntaiset molemmilla sukupuolilla ja osoittivat, että kettu käyttävät seinättömiä hyllyjä merkitsevästi (p<0,01) enemmän kuin seinällisiä hyllyjä sekä hyllylle hyppelyyn (kesto < 1 min) että lyhytaikaiseen lepäilyyn (kesto 1-10 min). Myös nukkumisen (kesto >l0 min) osalta tulos oli pääosin samansuuntainen. Ainut poikkeus oli syyskuu, jolloin naaraat nukkuivat molemmissa hyllytyypeissä yhtä paljon. Häiriötesti osoitti, että akuutissa voimakkaassa häiriötilanteessa kettu välttävät hyppäämistä seinällisiin hyllyihin, koska ne eivät näe niistä ympäristöön. Tulosten perusteella voidaan todeta, että ympäristön tarkkailun mahdollisuus on ketuille tärkeä, ja siksi ne suosivat seinättömiä hyllyjä. Euroopan neuvoston (1991) määräyksiä on näiltä osin syytä muuttaa.

The current European recommendations require that platforms in the cages of farm foxes should have solid sides. The present study aimed to clarify how such a obstructed view affects platform use in farmbred blue foxes (Alopex lagopus). Experimental groups with open (16 males, 14 females) and walled (16 males, 14 females) platforms were compared from weaning to pelting. Both platform types were 110 em long x 30 em wide. Walled platforms had 23 em high walls at the ends and rear, but open ones were without walls. Data were collected by daytime scanning observations and 24-h video recordings. Results for both sexes were parallel, showing that foxes significantly (p<0.001) prefer open platforms over walled types. Video recordings revealed a significantly (p<0.01) greater use of open platforms for jumping and resting (short duration 1-10 min on platform) compared to walled platforms. A rather parallel conclusion was found for sleeping also. The only exception was in September when females given both platform types slept on them for the same amount of time on average. The disturbance test showed that foxes supplied with open type platforms jumped onto them significantly (p<0.05) more often (62.5% of males, 85.7% of females) than those given the walled type (25.0% of males, 35.7% of females). It can be concluded that foxes avoid platforms with walls because such platforms prevent observation of the surroundings and therefore the possibility to adjust their distance to danger.
Keywords: ko; makuuhylly; Alopex lagopus; turkiseläimet; kettu; etologia; resting shelf; view; farm fox; animal welfare; environmental enrichment